Preparation of ZSM5 from Several Types of Coal Fly Ash using Hydrothermal Method for Catalytic Pyrolysis using Heat Pipe as a Passive Cooling for High-Density Polyethylene Waste - Desy Kurniawati, Nandy Putra, Nasruddin Abdullah, Agus Nurrokhmat (International Journal of Advanced Science and Technology, 2020)
Plastic waste processing technology is advancing to minimize the growing plastic waste today. HDPE (high-density polyethylene), one type of plastic that is widely used in our daily lives, representing plastic waste that takes a long time to unravel naturally. This study discusses the preparation of the ZSM5 catalyst as the main component, which is made from several types of Indonesian coal fly ash. It will be used to convert HDPE waste into diesel fuel using low energy pyrolysis technology with liquid collection system. The pyrolysis process used is a thermal pyrolysis with a passive cooling system, consisting of several straight heat pipes, which are run for the raw material 50g on the temperature process done at 500 and 550 °C in 3 hours. Therefore, ZSM5 as a catalyst is necessary to aid the process of converting plastic waste to diesel fuel, which is expected to have the same characteristics as diesel by developing thermal pyrolysis for catalytic pyrolysis. ZSM5 as catalysts are also made from the power plants’ fly ash of the four different types of coal, namely Amurang, Bukit Asam, Adaro and Kidenco. Furthermore, the best type of fly ash is selected to create ZSM5. The minimum Si/Al ratio is 5, ideally in the range of 5- 50. The ratio value of the fly ashes of Amurang, Bukit Asam, Adaro, and Kidenco are 21.95,10.02, 2.40, and 3.79, respectively. Thus, Amurang and Bukit Asam fly ashes were selected to be formed into ZSM5. In the next step, Amurang and Bukit Asam fly ashes are processed by hydrothermal methods to remove impurities by using 10 M HCl which is heated at 550oC for 1 hour to obtain Supernatan solution, then added sodium dodecyl sulfate (SDS) 0.21 M and NH4OH until reaches PH of 9.5-10. The fly ash is then heated in the oven at a temperature of 97 oC for 5 days, and then heated again for 5 days in an oven with a temperature of 550 oC. BET (Brunaeur-Emmet-teller) test as a test characteristic catalyst is performed on the results ZSM5. The results of ZSM5 BET test showing the surface area of Amurang fly ash (9.11 m2/g); Bukit Asam fly ash (21.25 m2/g), volume of pore Amurang fly ash (0.02 ml/g); Bukit Asam fly ash (0.03 ml/g), and the pore size Amurang fly ash (40.12 Å); Bukit Asam fly ash (25.93 Å). From these results it can be stated that the pore size matches the characteristics of ZSM5.